The The Role of CLT in Promoting Learner Autonomy in English Language Classrooms: A Case Study on Bangladeshi Tertiary Education - A.F.M Sadman Sakib Fuad (Universitas Ahmad Dahlan, 2023)
Exploratory in nature, this study aims to discover how CLT is interconnected with learner autonomy and whether it effectively propagates autonomy in tertiary-level ELT classrooms of Bangladesh. A mixed-method approach is followed to conduct this research. Two separate sets of questionnaires have been developed and distributed among the tertiary teachers and students to collect the quantitative data. Additionally, the qualitative data is extracted from the semi-structured interviews of the tertiary students. The major findings of this current study conclude with four essential themes: collaborative learning, teachers’ role in tertiary CLT classrooms, autonomous learners, and freedom of learning with CLT. Moreover, the detailed analysis of these themes evaluates Bangladeshi tertiary students’ stance on CLT and affirms that CLT is quite sufficiently promoting learner autonomy in tertiary ELT classes. At last, the study concludes with a set of recommendations for tertiary teachers so that they can be more efficient in replicating CLT methods in language classrooms to ensure the everlasting display of autonomy.